Evaluation of the Role of Serum Malondialdehyde in the Pathogenesis of Diabetic Retinopathy - زينة محمد حسن; رنا علي حمدي; ابتهال نوري البصام (مجلة كلية الطب, 2022)
Background:  The most typical consequence of diabetes mellitus is diabetic retinopathy. An important part of the etiology of diabetes and diabetic retinopathy is played by oxidative stress. Malondialdehyde is a dialdehyde that is moderately toxic and is frequently used as a marker for oxidative stress as well as lipid peroxidation.